The Problem Of Developing The Research Competence Of Special Educators - Yerzhanova, Gulnur; Autaeva, Aibota Nursultanova
The article deals with the problem of developing the research competence of special educators. The article analyzes foreign and domestic experiences in the development of research competence. The essence of the concept of research competence is revealed, and its features and capabilities are defined and disclosed. The characteristics of the concepts of competence, competence approach, and research competence are given. Research competence is the formation of skills necessary for carrying out research activities, and the presence of motivation for scientific activity It is characterized by achieving the result necessary to achieve the set goals, planning, designing, conducting research, discussing and demonstrating their results. Research objectives: to identify the theoretical and methodological foundations of the problem of developing the research competence of special teachers; to systematize the methodological foundations of the problem of developing the research competence of special teachers. The purpose of the study: theoretical methodological substantiation of the problem of developing the research competence of special teachers, the development of a methodology and experimental verification of its effectiveness. In order to identify the effectiveness of the problem of developing the research competence of special teachers, an ascertaining experiment and a questionnaire survey of students were conducted. Based on the results of the survey, the levels and content of the problem of developing the research competence of special teachers were determined. The results have been verified and displayed on the chart.
Keywords: Education